2019
DOI: 10.3390/met9050566
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Laser Quenching on Fretting Fatigue Life

Abstract: Laser quenching hardening is one of the most used surface treated technologies. In order to study the effect of laser quenching on the fretting fatigue life, fretting fatigue experiments of TC11 (Ti-6.5Al-1.5Zr-3.5Mo-0.3Si) titanium alloy specimens with different surface conditions were carried out on a special hydraulic servo fatigue test system. The experimental results showed that laser quenching hardening has a good performance in increasing the fretting fatigue lives of the TC11 alloy. However, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The errors in the predicted life compared to the test life were within a factor of two error bands, demonstrating the validity of the life prediction model. According to research by Zhang et al [25], laser quenching hardening had a more noticeable impact at low-stress levels than it did at high-stress levels on the fretting fatigue characteristics of theTC11 alloy. The traditional SWT (Smith-Watson-Topper) parameter was updated and utilized to describe the fretting fatigue life of the TC11 alloy after hardening.…”
Section: Introductionmentioning
confidence: 98%
“…The errors in the predicted life compared to the test life were within a factor of two error bands, demonstrating the validity of the life prediction model. According to research by Zhang et al [25], laser quenching hardening had a more noticeable impact at low-stress levels than it did at high-stress levels on the fretting fatigue characteristics of theTC11 alloy. The traditional SWT (Smith-Watson-Topper) parameter was updated and utilized to describe the fretting fatigue life of the TC11 alloy after hardening.…”
Section: Introductionmentioning
confidence: 98%
“…Yang et al [33] improved the fretting fatigue life of TC11 titanium alloy by laser shock peening, and suggested that the fretting fatigue cracks were mainly nucleated in β phase. Zhang et al [34] investigated the effect of laser quenching on the fretting fatigue properties of TC11 titanium alloy. And proved that the SWT model is accurate in predicting the low-cycle fretting fatigue life of TC11 titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the original design configuration of many components is difficult to change, the research on surface protection techniques of fretting fatigue has been developed since the 1960s, and some techniques have been applied successfully [ 4 ]. The principle of most surface protection techniques, such as coating and shot peening, is to introduce residual compressive stress into the contact surface, reduce the friction coefficient of the contact surface, and improve the hardness and wear resistance of the contact surface [ 5 , 6 , 7 , 8 , 9 , 10 ]. As an advanced surface treatment, laser shock peening (LSP) which induces the deep compressive residual stresses beneath the contact surfaces has been proved to be significantly beneficial to improve the fretting fatigue lives [ 11 ].…”
Section: Introductionmentioning
confidence: 99%